THE EMOTIONAL EXPERIENCES OF SENIOR HIGH SCHOOL STUDENTS IN LEARNING ENGLISH USING ONLINE PLATFORM DURING THE COVID-19 - Nurlita Malota; Aminah Suriaman; Mukrim Mukrim; Zarkiani Hasyim; Anjar Kusuma Dewi (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
The aim of this study was to find out the emotional experiences of students in online learning English using an online platform in the middle of Covid-19. The research was a single case study. Data were garnered from the results of interviews and documents. The participants in this study were three students at a senior high school in Luwuk, Central Sulawesi. The researcher analyzed the data thematically as proposed by Braun Clarke (2006). The finding showed that online learning English affected the emotional experiences of the students. The students experienced a positive emotion, i.e happiness. The happiness feeling was driven by the provision of feedback and explanation by teachers before giving tasks, allowing the students to send their tasks on the platform they wanted, explaining the materials through Zoom Application, and did not provide tasks in each meeting. However, they also experienced negative emotions such as frustration, anger, and anxiety in English learning using an online platform. They perceived frustration because online English learning was difficult for them. In this case, they had to purchase internet quota, did not meet in person with the teacher, had limitations of time, felt bored due to frequent use of Zoom Meeting, experienced many disturbances, such as; their smartphones’ memory filled up fast because of getting many files from their teachers. Consequently, the negative emotions decreased the students’ time invested and the amount of knowledge gained from the learning process. The study implies that learning English using an online platform influenced students’ emotions